Pediatric biorepository participation during the COVID-19 pandemic: predictors of enrollment and biospecimen donation - Anne M. Neilan; Anisha Tyagi; Yao Tong; Eva J. Farkas; Madeleine D. Burns; Allison Fialkowski; Grace Park; Margot Hardcastle; Elizabeth Gootkind; Ingrid V. Bassett; Fatma M. Shebl; Lael M. Yonker (BMC, 2022)
Abstract Background Patient-level predictors of enrollment in pediatric biorepositories are poorly described. Especially in pandemic settings, understanding who is likely to enroll in a biorepository is critical to interpreting analyses conducted on biospecimens. We describe predictors of pediatric COVID-19 biorepository enrollment and biospecimen donation to identify gaps in COVID-19 research on pediatric biospecimens. Methods We compared data from enrollees and non-enrollees aged 0-25 years with suspected or confirmed COVID-19 infection who were approached for enrollment in the Massachusetts General Hospital pediatric COVID-19 biorepository between April 12, 2020, and May 28, 2020, from community or academic outpatient or inpatient settings. Demographic and clinical data at presentation to care were from automatic and manual chart extractions. Predictors of enrollment and biospecimen donation were assessed with Poisson regression models. Results Among 457 individuals approached, 214 (47%) enrolled in the biorepository. A COVID-19 epidemiologic risk factor was recorded for 53%, and 15% lived in a US Centers for Disease Control and Prevention-defined COVID-19 hotspot. Individuals living in a COVID-19 hotspot (relative risk (RR) 2.4 [95% confidence interval (CI): 1.8-3.2]), with symptoms at presentation (RR 1.8 [95% CI: 1.2-2.7]), or admitted to hospital (RR 1.8 [95% CI: 1.2-2.8]) were more likely to enroll. Seventy-nine percent of enrollees donated any biospecimen, including 97 nasopharyngeal swabs, 119 oropharyngeal swabs, and 105 blood, 16 urine, and 16 stool specimens, respectively. Age, sex, race, ethnicity, and neighborhood-level socioeconomic status based on zip code did not predict enrollment or biospecimen donation. Conclusions While fewer than half of individuals approached consented to participate in the pediatric biorepository, enrollment appeared to be representative of children affected by the pandemic. Living in a COVID-19 hotspot, symptoms at presentation to care and hospital admission predicted biorepository enrollment. Once enrolled, most individuals donated a biospecimen.